RASIO KEUANGAN DAN PREDIKSI FINANCIAL DISTRESS - Jenny Pratiwi Assaji; Zaky Machmuddah (Jurnal Penelitian Ekonomi dan Bisnis, 2017)
The purpose of this research is to understand the effect of financial ratios in predicting the possibility of financial distress on companies listed on Sri Kehati index in a row of 2009-2016. This study uses the financial ratios proxied by return on assets, return on capital, net profit margin, P / E ratio, and asset turnover as independent variables. Meanwhile, the financial distress proxied by Z-score is a dependent variable. The population of this study is all companies listed on the index of Sri Kehati in 2009-2016 and listed on the Indonesia Stock Exchange. The sample of this study took nine companies with purposive sampling method and the study period is for eight years in a row (2009-2016). Logistic regression method used in this research. The results show that ROA, ROE and PER have a significant effect on financial distress. Meanwhile, NPM and ATO have no significant effect on financial distress.Keywords: Financial Ratio;Financial Distress